2012
DOI: 10.1080/14634988.2012.709814
|View full text |Cite
|
Sign up to set email alerts
|

Application of satellite multi-sensor techniques to detect upwellings and potential fishing grounds in Wakatobi Marine National Park, Southeast Sulawesi, Indonesia

Abstract: Information about Yellowfin Tuna fishing grounds is needed to develop the capture fisheries sector, which could be obtained through satellite multi-sensor mapping techniques. Fishermen often have difficulty determining where the fish are and when they can be caught in abundance. Knowing this information would sufficiently reduce operating costs. Mapping the fishing ground of Yellowfin Tuna would also avoid overfishing due to the concentration of fishing boats in one particular location, thus allowing the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Similar results have been found elsewhere in Indonesia; Holmes et al (2000) found that bioeroding sponge occupation of massive corals correlated with chl- a concentration on polluted Javan reefs but not in Ambon where chl- a was less concentrated and more consistent across sites. The majority of our chl- a measurements deployments took place during the dry season (June–August) when chl- a concentration is at its highest (Tadjuddah et al , 2012). However, the broad scale seasonal upwellings that are responsible for this peak in chl- a (Wyrtki, 1961), might also mask inter-site variation in chl- a concentration from local sources.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been found elsewhere in Indonesia; Holmes et al (2000) found that bioeroding sponge occupation of massive corals correlated with chl- a concentration on polluted Javan reefs but not in Ambon where chl- a was less concentrated and more consistent across sites. The majority of our chl- a measurements deployments took place during the dry season (June–August) when chl- a concentration is at its highest (Tadjuddah et al , 2012). However, the broad scale seasonal upwellings that are responsible for this peak in chl- a (Wyrtki, 1961), might also mask inter-site variation in chl- a concentration from local sources.…”
Section: Discussionmentioning
confidence: 99%
“…Their knowledge about fishing grounds and migratory lanes of Tuna, especially Yellowfin Tuna (Thunnus albacares), is documented as the upwelling areas. Possibly, this TEK might be integrated with satellite mapping to increase the economic income of the Bajau in Wakatobi (Tadjuddah et al, 2012).…”
Section: Sustainable Resource Use and Bajau Tekmentioning
confidence: 99%